2000
DOI: 10.1177/002215540004800712
|View full text |Cite
|
Sign up to set email alerts
|

Immunolocalization of Tenascin-C, α9 Integrin Subunit, and αvβ6 Integrin During Wound Healing in Human Oral Mucosa

Abstract: Tenascin-C (TN-C) and its isoforms are multidomain extracellular matrix (ECM) proteins that are believed to be involved in the regulation of stromal-epithelial interactions. Some of the interactions between TN-C and cells are mediated by integrins. In this study we analyzed the expression of TN-C and its large molecular weight splice isoform (TN-C(L)) and the putative TN-C-binding alpha9 and alphavbeta6 integrins during human wound repair. In 3-day-old oral mucosal wounds, immunoreactivity for alpha9 integrin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
86
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(91 citation statements)
references
References 64 publications
5
86
0
Order By: Relevance
“…Cytokines, such as PDGF, granulocytemacrophage colony-stimulating factor (GM-CSF), heparin, integrin [20] , and TGF-β, and existing tractional forces stimulate protofibroblast differentiation through α-SMA expression, leading to their transformation into MFs. A study conducted on the role of tenacin in wound contraction demonstrated that increased tenacin expression correlated with MF differentiation [23] . However, interferon-γ, a basic fibroblast growth factor (bFGF), prostaglandin E2, and high cell density inhibit the differentiation of protofibroblasts to MFs [20] .…”
Section: Role Of Mfs In Wound Contractionmentioning
confidence: 99%
“…Cytokines, such as PDGF, granulocytemacrophage colony-stimulating factor (GM-CSF), heparin, integrin [20] , and TGF-β, and existing tractional forces stimulate protofibroblast differentiation through α-SMA expression, leading to their transformation into MFs. A study conducted on the role of tenacin in wound contraction demonstrated that increased tenacin expression correlated with MF differentiation [23] . However, interferon-γ, a basic fibroblast growth factor (bFGF), prostaglandin E2, and high cell density inhibit the differentiation of protofibroblasts to MFs [20] .…”
Section: Role Of Mfs In Wound Contractionmentioning
confidence: 99%
“…This finding is consistent with previous reports that ␣v␤6 is expressed at low levels in healthy adult epithelium but is up-regulated during tissue injury and repair. 10,11,13,15,17 …”
Section: Expression Of ␣V␤6 In Human Kidney Samples With Fibrotic Patmentioning
confidence: 99%
“…5,9,10 ␣v␤6 expression is generally restricted to epithelial cells where it is expressed at low levels in normal adult tissues and elevated during development, injury, and neoplasia. 9,[11][12][13] Although ␣v␤6 is expressed at relatively low levels in healthy adult kidney, its expression is prominent in the developing mouse kidney, particularly in the proximal tubules, loop of Henle, and collecting ducts. 11,12,14 Recently, elevated expression of ␣v␤6 has been reported for various forms of human kidney pathology.…”
mentioning
confidence: 99%
“…Against the background that there is also a reexpression of oncTn-C during fibrosis, wound healing, and tissue remodeling, the synthesis of Tn-C by fibroblasts / myofibroblasts / CAFs can be explained as a sign of cellular activation and may be linked also to the migratory capability of stromal cells. [31][32][33][34] Since Tn-C critically modulates cell adhesion to fibronectin and modulates fibronectin assembly by fibroblasts, stromal and tumor derived Tn-C may have the same function and the final situation is more or less determined by the quantity and site-specific modulation of the deposited protein. Recently, it was indeed shown that the capability of Tn-C to prevent fibrillogenesis of fibronectin by fibroblasts depends on proteolytic processing and demasking of cryptic domains.…”
Section: Invasion Associated Reorganization Of Tenascin-c -A Collabormentioning
confidence: 99%
“…77,78 Interestingly, in concordance with invasion of neoplastic keratinocytes, a comparable co-organization of oncTn-C and the integrins a9 and avb6 was shown in healing wounds speaking well for a comprehensive mechanism during epithelial migration. 31 Up to now there are only few reports on the differential expression and possible function of Tn-C splicing variants in OSCC. In 1997, Mighell and coworkers published an interesting study describing the mRNA expression of splicing domains in normal, malignant, and reactive oral mucosae.…”
Section: Tenascin-c In Oral Squamous Cell Carcinoma Invasionmentioning
confidence: 99%